Baicalein enhances the antitumor efficacy of docetaxel on nonsmall cell lung cancer in a β‐catenin‐dependent manner. (12th September 2019) - Lu, Linwei; Zhang, Mingfei; Wang, Xiaoyi; Zhang, Yanyu; Chai, Zhilan; Ying, Man; Guan, Juan; Gong, Weiyi; Zhao, Zhengxiao; Liu, Lumei; Hu, Yang; Lu, Weiyue; et al.
Abstract : The side effects of docetaxel have limited its antitumor performances in the treatment of nonsmall cell lung cancer (NSCLC). To address the problem, baicalein, a bioactive flavone that exhibits antitumor activity, was combined with docetaxel so as to achieve better efficacy and lower toxicity. The combination treatment enhanced the stabilization of microtubules and halted the cell‐cycle progression, thus synergistically inhibiting the proliferation and inducing the apoptosis of A549 cells and Lewis lung carcinoma cells. The decreased expression of Cyclin‐dependent kinase 6 and Cyclin B1 confirmed its regulation in cell cycle, with β‐catenin being an important upstream effector, as evidenced by the decreased expression in the cytoplasm and nucleus as well as the attenuated aggregation in the nucleus. Furthermore, baicalein plus docetaxel evinced better antitumor efficacy by the suppressed tumor growth, increased apoptosis, and decreased tumor angiogenesis in vivo, with no increased toxicity discovered in both tumor‐bearing and non‐tumor‐bearing mice, and an improvement in therapeutic index. This study has demonstrated that baicalein plus docetaxel is an appropriate combination simultaneously with augmented antitumor efficacy and acceptable safety, which might be a promising strategy for patients with advanced NSCLC. Abstract : Baicalein plus docetaxel displayed synergy in vitro, which was related with the decreased expression of β‐catenin and its attenuated aggregation in the nucleus. Baicalein plus docetaxel evinced better antitumor efficacy and no increased toxicity in vivo, showing an improvement in therapeutic index. Baicalein plus docetaxel might be a promising strategy for patients with advanced NSCLC.